Taxing Corporations in ASEAN: Exploring the Impact of Tax Rates on the Tax Base (2003-2022) - Yamin, Fawzyyah; Purwanti, Evi Yulia (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2026)
This study investigates the impact of corporate income tax rate (CIT) reductions on the corporate tax base in four ASEAN countries, Indonesia, Malaysia, Singapore, and Thailand, from 2003 to 2022. Despite CIT reductions aimed at attracting investment and enhancing competitiveness, corporate tax revenue in the region has stagnated, raising concerns about the effectiveness of these policies. Using a two-stage least squares (2SLS) regression with instrumental variables to address potential endogeneity, the study examines the relationship between the corporate tax base and various factors, including CIT rates, lagged corporate tax base, other countries' CIT rates, top personal income tax rates, export prices, labor costs, and economic growth. Findings reveal that the statutory corporate income tax rate does not have a statistically significant effect on the corporate tax base, suggesting that changes in headline tax rates alone do not explain variations in corporate taxable income in ASEAN countries. In contrast, the average corporate income tax rate of neighboring countries has a significant negative effect on the domestic tax base, indicating the presence of regional tax competition. Other control variables, including labor costs, export prices, and the top personal income tax rate, are statistically insignificant, suggesting that institutional and structural factors shape the corporate tax base. The study contributes by providing region-specific evidence that corporate tax base dynamics in ASEAN are shaped more by cross-border tax interactions and institutional persistence than by domestic rate adjustments. From a policy perspective, the findings suggest that strengthening tax administration, broadening the tax base, and enhancing regional coordination may be more effective than unilateral changes in statutory tax rates.